Perfluorooctanoic acid-induced developmental cardiotoxicity in an avian model - Jiang, Qixiao (East Carolina University, 2013)
Perfluorooctanoic acid (PFOA) is a synthetic chemical used in polyfluormer production. It is a widespread environmental contaminant and is known to induce developmental toxicity in rodent models. As several related compounds also induce developmental cardiotoxicity in avian models, a series of experiments were carried out in chicken embryos and hatchling chickens to assess the effects of PFOA on developing hearts and to explore underlying mechanisms. Histology was used to assess late stage embryo hearts and echocardiography was used to assess morphological and functional parameters of hearts in living one-day-old hatchlings. Hearts of exposed embryos had a thinned right ventricular wall and multiple morphological and functional changes were detected in the left ventricles of exposed hatchlings. As PFOA is known to activate the peroxisome proliferator activated receptor á (PPARá) in rodent models, the PPARá agonist WY 14,643 was used to assess the role of PPARá in PFOA-induced developmental cardiotoxicity. Real-time polymerase chain reaction (PCR) and western blot were used to assess hearts of early stage embryos for expression of genes related to heart development. WY 14,643 partially mimicked the morphological and functional effects of PFOA only in the left ventricle of hearts of hatchling chickens and bone morphogenic protein 2 (BMP2) signaling pathways were involved in mediating the process. Additionally, primary cardiomyocyte cultures were used to explore mechanisms of toxicity at the cellular level. Viability, contractility, and reactive oxygen species (ROS) generation were evaluated in primary cardiomyocytes isolated from hearts of embryos exposed to PFOA in ovo or were exposed in vitro. Primary cardiomyocytes isolated from embryos exposed to PFOA in ovo functioned similarly to hearts of exposed hatchling chickens. Primary cardiomyocytes exposed in vitro responded differently, suggesting that the cardiotoxicity is likely from interference of PFOA in an early stage of heart development rather than from overt cytotoxicity to cardiomyocytes. In conclusion, this dissertation work indicates that PFOA induces morphological and functional alterations in hearts of chicken embryos and hatchling chickens, that mechanisms of the cardiotoxicity may involve PPARá and BMP2 signaling pathways, and that PFOA is likely interfering in an early stage of heart development.
Keywords: Toxicology; Avian; Cardiotoxicity; Developmental toxicity; Perfluorooctanoic acid; Fluorocarbons--toxicity; Chick Embryo--embryology; Heart--embryology; Models, Animal